Impact of leaf spot disease on beetroot production in Jaffna peninsula, Sri Lanka - Nivetha, S.; Christy Jeyaseelan, E. (Taylor & Francis Group, 2022)
The present study focuses on the aetiology of leaf spot disease and its impact on beetroot production in the Jaffna peninsula. A survey and field study was carried out to under stand present status of the disease. The fungus associated with the leaf spot lesions was isolated and identified based on morphological features and sequence analysis. The survey has shown drawbacks in the cultivation practices, such as selection of cultivation season, selection of variety and inad equate weed management practices. The initial symptoms were noted in seedling stage, and the disease incidence and severity progressed with time. The disease incidence and severity index were 85% and 2.71 at 48days. The field exper iment has revealed the negative correlation between leaf spot disease development and yield. The fungal isolates produced obclavate shape, hyaline, multiseptated conidia on dark coloured unbranched sparingly septate conidio phores. The isolates showed 99.25% sequence identity with Cercospora beticola.
Keywords: Beetroot; Cercospora sp; Jaffna peninsula; Leaf spot disease; Survey